Rethinking Rail Track Switches for Fault Tolerance and Enhanced Performance. Issue 21 (2016) - Harrison, Tim; Bemment, Samuel D.; Ebinger, Emma; Goodall, Roger M.; Ward, Christopher P.; Dixon, Roger
Abstract: Railway track switches, commonly referred to as 'turnouts' or 'points', are a necessary element of any rail network. However, they often prove to be performance limiting elements of networks. A novel concept for rail track switching has been developed as part of a UK research project with substantial industrial input. The novel design meets the set of functional requirements for track switching solutions, in addition to offering several features that current designs are unable to, in particular to enable multi-channel actuation and rail locking, and provide a degree of fault tolerance. This paper describes the design and operation of this switching concept, from requirements capture and solution generation through to the construction of the laboratory demonstrator. The novel concept is contrasted with the design and operation of the 'traditional' switch design. Conclusions to the work show that the novel concept meets all functional requirements whilst exceeding the capabilities of existing designs in most non-functional requirement areas.